Surabaya towards a smart city constrained by COVID-19 - Akhmad Yusuf ZUHDY; Aan FAUZI (Smart Cities and Regional Development Journal)
Surabaya, East Java is one of the cities in Indonesia which is well known as a Smart City. This achievement can not be separated from the breakthroughs and innovations that the local City Government (Pemkot) has made. The city government of Surabaya has also received various awards from within and outside the country, especially in the field of smart city. One of the awards is the 2018 OpenGov Recognition of Excellence. However, when the smart city was being helded, a pandemic emerged that attacked almost all parts of the world. This study aims to identify obstacles and steps to deal with Covid-19 without disturbing the stability of Surabaya towards a smart city. The data were obtained from social media from the Surabaya municipal government and the smart city parameters were taken from academic papers. The concept of smart city according to Surabaya begins with Smart Government, namely by implementing an internet-based government system which is also known as e-procurement. Other parameters are smart branding, smart economy, smart living, smart society, smart environment. This paper focuses on discussing smart environment without neglecting other parameters. Unfortunately, since the Covid-19 pandemic Surabaya has become the city in Indonesia with the most corona cases after Jakarta and Bogor with confirmed positive data up to November 1, 2020, amounting to 15,973 cases. The Surabaya City Government (Pemkot Surabaya) has implemented various efforts in order to prevent or break the chain of the spread of COVID-19. Consists of promotive, preventive, curative and rehabilitative efforts.